"One Muslim is enough!" Evidence from a field experiment in France - Claire L. Adida; David D. Laitin; Marie-Anne Valfort (Institute for the Study of Labor (IZA), 2011)
Anti-Muslim prejudice is widespread in Western countries. Yet, Muslims are expected to constitute a growing share of the total population in Western countries over the next decades. This paper predicts that this demographic trend will increase anti-Muslim prejudice. Relying on experimental games and a formal model, we show that the generosity of rooted French toward Muslims is significantly decreased with the increase of Muslims in their midst, and demonstrate that these results are driven by the activation of rooted French taste-based discrimination against Muslims when Muslim numbers increase. Our findings call for solutions to anti-Muslim prejudice in the West.
urn:nbn:de:101:1-201111303547
Keywords: A12; C90; D03; J15; J71; Z12; 330; discrimination; Islam; France; group salience; experimental economics; economic theory; group threat theory; intergroup contact theory; Ethnische Diskriminierung; Muslime; Feldforschung; Frankreich